Duck cGAS inhibits DNA and RNA virus replication by activating IFNs and antiviral ISGs - Lin, Chang; Zheng, Min; Xiao, Shifeng; Wang, Shao; Zhu, Xiaoli; Chen, Xiuqin; Jiang, Dandan; Zeng, Xiancheng; Chen, Shaoying; Chen, Shilong (Frontiers in Immunology, 2023)
Cyclic GMP-AMP Synthase (cGAS) is a pivotal adaptor of the signaling pathways involving the pattern recognition receptors and plays an important role in apoptosis and immune regulation. The cGAS function in mammals has been investigated extensively; however, the function of duck cGAS (du-cGAS) in response to viral infections is still unclear. This study aimed to clone the mallard (Anas platyrhynchos) cGAS homolog to investigate the function of duck cGAS (du-cGAS) in host antiviral innate immunity. The results showed that the open reading frame (ORF) region of the ducGAS gene was 1296 bp, encoding 432 amino acids (aa) and exhibiting similar functional domains with its Gallus counterpart. Knockdown of the endogenous ducGAS by specific sgRNA strongly increased the replication of DNA viruses, including duck adenovirus B2 (DAdV B2) and duck short beak and dwarfism syndrome virus (SBDSV). However, the knockout did not impair the replication of novel duck reovirus (NDRV), an RNA virus. Furthermore, the mRNA expressions of type I interferon (IFNs) and vital interferon-stimulated genes (ISGs) were remarkably reduced in the du-cGAS knockout DEF cell line. Inversely, du-cGAS overexpression greatly activated the transcription of IFN-a, IFN-β, and vital ISGs, and impaired the replication of DAdV B2, SBDSV, and NDRV in the DEF cell line. Importantly, we found that a deletion of 68 aa in the N terminus didn’t impair the antiviral function of du-cGAS. Overexpressing NTase Core, C-Domain (Mab21), or Zinc-Ribbon domain independently had no antiviral effects. Generally, these results reveal that ducGAS is a vital component of the innate immune system of ducks, with a universal antiviral activity, and provides a useful strategy for the control of waterfowl viral diseases.